2020
DOI: 10.1261/rna.073395.119
|View full text |Cite
|
Sign up to set email alerts
|

5′ tRNA halves are highly expressed in the primate hippocampus and might sequence-specifically regulate gene expression

Abstract: Fragments of mature tRNAs have long been considered as mere degradation products without physiological function. However, recent reports show that tRNA-derived small RNAs (tsRNAs) play prominent roles in diverse cellular processes across a wide spectrum of species. Contrasting the situation in other small RNA pathways the mechanisms behind these effects appear more diverse, more complex and are generally less well understood. In addition, surprisingly little is known about the expression profiles of tsRNAs acr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…The role of these tsRNAs and whether they function in downstream signaling pathways requires further investigation in the near future. Although there are studies where synthetic tsRNAs are used to evaluate their biological potential [ 15 , 21 , 53 ], recent evidence demonstrates that endogenous tsRNAs also bear particular modifications as they derive from modified mature tRNAs [ 38 ]. As RNA modifications impact on RNA interaction with proteins, future studies on tsRNA function should be performed with modified molecules, as recently suggested and demonstrated for the two most abundant tiRNAs often found in cells in response to stress, and that coincide with the most expressed tiRNAs found in this study, namely 5′tiRNA-Gly GCC and 5′tiRNA-Glu CTC [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of these tsRNAs and whether they function in downstream signaling pathways requires further investigation in the near future. Although there are studies where synthetic tsRNAs are used to evaluate their biological potential [ 15 , 21 , 53 ], recent evidence demonstrates that endogenous tsRNAs also bear particular modifications as they derive from modified mature tRNAs [ 38 ]. As RNA modifications impact on RNA interaction with proteins, future studies on tsRNA function should be performed with modified molecules, as recently suggested and demonstrated for the two most abundant tiRNAs often found in cells in response to stress, and that coincide with the most expressed tiRNAs found in this study, namely 5′tiRNA-Gly GCC and 5′tiRNA-Glu CTC [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms for the regulation of gene expression by such tRNA fragments have been described, including repression of translation by inhibiting the assembly of the translation initiation machinery, or a sequence-specific gene regulation. However, sufficient understanding of how these fragments regulate gene expression is still lacking [ 122 ]. As 5′ tRNA halves may regulate mRNA translation, Dhahbi et al suggested their function as signaling molecules [ 121 ].…”
Section: Cell-free Rnamentioning
confidence: 99%
“…tsRNAs have been shown to exhibit tsRNA-mediated transcriptional silencing that is dependent on a 5 seed, such that the structure of AGO facilitates the 5 end of small RNAs for target recognition (Boland et al, 2011), which is complementary to target sites within the 3 UTR (Haussecker et al, 2010). The results of these studies suggest that tsRNAs regulate the expression of genes by targeting various mRNA interactions with other effector proteins or by acting protein-independently (Jehn et al, 2020). Because tsRNAs have only recently been discovered, a database for tsRNA target prediction has not been available.…”
Section: Discussionmentioning
confidence: 97%